(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This article aims to report 02 rare cases of chronic glossopharyngeal neuralgia (9th nerve), treated by nerve block, thereby reviewing the literature. Case report: 02 patients were both misdiagnosed as 5th neuralgia on magnetic resonance imaging (MRI). However, the clinical symptoms are typical of 9th nerve pain. We used the 9th nerve block technique for two patients, achieving good pain relief and no complications during and after the procedure. Discussion: The discussion focuses on the definitive diagnosis, differential diagnosis and some minimally invasive interventional treatments of 9th neuralgia, emphasizing the effectiveness of these interventional methods. Conclusion: Chronic 9th neuralgia is a very rare disease that can be treated with nerve block technique.